A Countdown to Orthognathic Surgery - Kapse, Bhagwat Rao; Kallury, Amitabh; Chouksey, Ankur; Shrivastava, Trilok; Sthapak, Ashutosh; Malik, Nidhi (Journal of Orofacial Research, 2015)
For patients whose orthodontic problems are so severe that neither growth modification nor camouflage offers a solution, surgery to realign the jaws or reposition dentoalveolar segments is the only possible treatment. Surgery is not a substitute for orthodontics in these patients. Instead, it must be properly coordinated with orthodontics and other dental treatment to achieve good overall results.